Dielectric Properties Of Virgin Coconut Oil - Mat Sauki, Siti Syafiqah (Universiti Sains Malaysia, 2018)
The transformer has become one of the most important equipment in electrical power system, especially in power distribution system. Therefore, the application of liquid insulator such as mineral oil (most commonly used) is very important to reduce the failure, ageing effect, increase the life span and act as a cooling medium (heat transfer agent). Mineral oil has a good dielectric strength and cooling performance, but it has serious negative environmental impact such as non biodegradable, non-renewable resource and difficult to dispose when the mineral oil deteriorates completely. As a result, three tests, breakdown voltage, water content and viscosity are carried out to investigate the dielectric properties of virgin coconut oil since it biodegrades completely without toxic and easy to obtain in the tropical country. However, the moisture ingress into the insulation oil can alter the hydrocarbon bond of the fatty acid and lowering the breakdown voltage. Therefore, this paper presents a study about the effect of the moisture level of VCO on breakdown voltage and kinematic viscosity. The breakdown voltage (BDV) is conducted according to IEC 601566 standard, while water content and kinematic viscosity follow ASTM D1533 and ASTM D445 respectively. The result obtained for BDV, water content and viscosity of VCO are 22.9kV 1235ppm and 22.9cSt respectively. However, dry VCO has higher BDV which is 99.8 kV. Also, the decrease of breakdown voltage was proportional to the increase of moisture, but the kinematic viscosity was slightly changed. The kinematic viscosity of mineral oil varied ±1.282% in descending order while VCO varied (-0.873 to 1.31) % in ascending order. These happened due to the high intermolecular forces in VCO. Then, the rate of breakdown voltage decrease with the increasing of moisture for VCO is lower than mineral oil. Therefore, the VCO has good breakdown voltage with the ability to absorb a lot of moisture keeping the Kraft paper dry. However, high kinematic viscosity making it not favorable to be used as insulation in transformer.